VOICES OF UNITY: THE ROLE OF RADIO STATIONS IN PROMOTING SHARED VALUES AND CULTURAL UNDERSTANDING IN NIGERIAN SOCIETY - Margaret Oghie Zibaghafa (PT. Antis International Publisher, 2026)
Objective: To assess the regulatory and structural challenges that face community radio stations in Nigeria and how these challenges undermine their ability to foster intercultural dialogue and strengthen national unity. Method: The study used a qualitative research design based on secondary sources, including textbooks, peer-reviewed journal articles, and governmental reports, which underwent strict content analysis. Results: Regulatory barriers, such as high licensing charges, obscure frequency allocation, and slow bureaucracy, limit community radio formation. Structural challenges, including inadequate infrastructure, funding shortages, and political influence, hinder culturally relevant programming and the potential for promoting intercultural dialogue and national unity. Novelty: The paper recommends policy changes to eliminate regulatory barriers, raise funds for infrastructure, and ensure political independence, including inclusive licensing, financial incentives, and editorial independence for community radio stations.